2012
DOI: 10.1371/journal.pone.0038945
|View full text |Cite
|
Sign up to set email alerts
|

NuMA Overexpression in Epithelial Ovarian Cancer

Abstract: Highly aneuploid tumours are common in epithelial ovarian cancers (EOC). We investigated whether NuMA expression was associated with this phenomenon.NuMA protein levels in normal and tumour tissues, ovarian cell lines and primary cultures of malignant cells derived from ovarian ascitic fluids were analysed by Affymetrix microarray analysis, immunoblotting, immunohistochemistry (IHC) and immunofluorescence (IF), with results correlated to associated clinical data. Aneuploidy status in primary cultures was deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Interestingly, these genes have all been associated with cancer risk. For example, mutations in ARHA1 ( RHOA ) have been repeatedly associated with risk of diffuse gastric cancer [45;46]; NUMA over expression has been significantly associated with disease stage and local metastases to lymph nodes in ovarian cancer [47]; and LCN2 , after the activation of the PI3/AKT/NFkB [48], has been shown to form complexes with MMP9 and these, in turn, being associated with reduced survival in gastric cancer [49;50]. Since progression to more advanced gastric lesions may be associated with the development of gastric cancer, and because previous studies had suggested that CD44 may be a marker of advanced gastric lesions [34;35], we wanted to investigate the role of this gene in development of gastric lesions.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, these genes have all been associated with cancer risk. For example, mutations in ARHA1 ( RHOA ) have been repeatedly associated with risk of diffuse gastric cancer [45;46]; NUMA over expression has been significantly associated with disease stage and local metastases to lymph nodes in ovarian cancer [47]; and LCN2 , after the activation of the PI3/AKT/NFkB [48], has been shown to form complexes with MMP9 and these, in turn, being associated with reduced survival in gastric cancer [49;50]. Since progression to more advanced gastric lesions may be associated with the development of gastric cancer, and because previous studies had suggested that CD44 may be a marker of advanced gastric lesions [34;35], we wanted to investigate the role of this gene in development of gastric lesions.…”
Section: Resultsmentioning
confidence: 99%
“…In parallel, we also performed immunohistochemistry in cross sections of testes transplanted with human fetal testis cells. In order to detect all human donor cells in recipient testes, we assessed expression of NuMA (Figure 3D), a well-characterized protein that exclusively labels human cells and tissues (Abad et al, 2007; Bruning-Richardson et al, 2012; Saadai et al, 2013). We observed significant human germ cell engraftment eight weeks post-transplantation (Figure 3C, iii).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, a recent study showed that NuMA is over‐expressed in human epithelial ovarian cancer (Bruning‐Richardson et al . ). As the pRB/pRB pathway was also shown to be altered in human high‐grade serous epithelial ovarian cancer (Szabova et al .…”
Section: Discussionmentioning
confidence: 97%